Pengaruh Kemampuan Kerja terhadap Kinerja Personel Polres Tuban yang Dimediasi oleh Pengembangan Karier : (Studi pada Satlantas Polres Tuban) - Chamariyah Chamariyah; Woro Utari; Anwar Shodiq (Universitas 45 Surabaya, 2025)
This type of research is explanatory research, the approach used is a quantitative approach, the research sample is 85 people. The analysis tool uses Smart PLS (Partial Least Square). Research objectives: 1) To determine and analyze the influence of work ability on the performance of Tuban Police Traffic Unit personnel. 2) To determine and analyze the influence of work ability on the career development of the Tuban Police Traffic Unit.. 3) To determine and analyze the influence of career development on the performance of Tuban Police Traffic Unit personnel. 4) To determine and analyze the indirect influence of work ability on the performance of Tuban Police Traffic Unit personnel which is mediated by career development. The research results show that: 1) Work ability has a positive and significant effect on personnel performance as evidenced by the original sample value of 0.369 and p-values ​​of 0.000. 2) Work ability has a significant positive effect on career development as proven by the original sample value of 0.373 and p-values ​​of 0.002. 3) Career development has a significant positive effect on personnel performance as evidenced by the original sample value of 0.378 and p-values ​​of 0.000. 4) Work ability has a positive and significant effect on personnel performance which is mediated by career development as evidenced by the original sample value of 0.141 and p-values ​​of 0.013.